Permasalahan Asesmen Pada Kurikulum Merdeka - Eni Astuti, Ni Putu; Margunayasa, I Gede; Suarni, Ni Ketut; Wirawan, I Putu Hendra; Sulastra, Putu (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine assessment problems in the independent curriculum. This research is qualitative research. The research subjects were teachers at SDN 1 Melinggih Kelod, Gianyar Regency, Bali, which was implementing the independent curriculum. Data collection techniques in this research are (1) observation, (2) interviews, and (3) expert discussions. The data analysis technique in this research uses an interactive model, namely (1) data reduction, (2) data presentation, (3) drawing conclusions. The research results show that there are two problems in assessment in the independent curriculum, namely 1) assessment problems in intracurricular learning and 2) problems in the Project for Strengthening the Pancasila Student Profile (P5). The problems with assessment in intracurricular learning consist of (1) teachers have not been able to differentiate between formative and summative assessments, (2) in formative assessments, teachers assume that the form of tests used are written tests only, (3) in summative assessments, teachers understand that assessments The summative is prepared by the teacher, but in fact it is still prepared by the education office, and (4) the teacher still considers report cards to determine learning outcomes. The problem with the P5 assessment concerns teachers' misconceptions that the P5 assessment is the final assessment carried out during harvest activities. This misconception gives rise to new problems in the field of financing where schools experience problems in harvesting work events which require money to organize.